2020
DOI: 10.2147/cmar.s259077
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Exosome-Encapsulated MicroRNA-21 from Esophageal Squamous Cell Carcinoma Cells Enhances Angiogenesis of Human Umbilical Venous Endothelial Cells by Targeting SPRY1</p>

Abstract: Objective Esophageal squamous cell carcinoma (ESCC) persists among the most prevalent cancers worldwide. Angiogenesis represents a crucial element necessitated for tumor growth and metastasis in ESCC. In this study, we aimed to study the effect of microRNA (miR)-21 on angiogenesis in ESCC and its underlying mechanism. Materials and Methods Initially, the expression patterns of miR-21, SPRY1, and VEGF were determined in ESCC tissues and cells. The relationship between mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…CCK-8 kit (MAO218, Meilun Biomeilunbio® Company, Dalian, China) was used. After seeding in 96-well plates, HUVECs were added with 10% CCK-8 reagent on the 1, 2, 3, 4, and 5 d, and incubated for 2 h. A microplate reader (Stat Fax 2100; Awareness, USA) was employed to measure the optical density 450 nm [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…CCK-8 kit (MAO218, Meilun Biomeilunbio® Company, Dalian, China) was used. After seeding in 96-well plates, HUVECs were added with 10% CCK-8 reagent on the 1, 2, 3, 4, and 5 d, and incubated for 2 h. A microplate reader (Stat Fax 2100; Awareness, USA) was employed to measure the optical density 450 nm [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, compared with normal exosomes, hypoxic exosomes have played a unique role in facilitating the aggressive behavior of human umbilical vein endothelial cells (HUVECs) both in vitro and in vivo , and HUVECs exposed to hypoxic exosomes induce enhanced proliferation, metastatic dissemination, and vessel formation ability in ESCC ( 86 ). Consistent with that study, Zhuang showed that ESCC cell-derived exosomal miRNA-21 potentiates the angiogenesis ability of HUVEC by targeting sprouty RTK signaling antagonist 1 (SPRY1) in ESCC ( 60 ). Moreover, exosomal miRNA-21-5p has been shown to significantly promote the angiogenesis of targeted cells via the activation of programmed cell death 4 and downgrading of the signaling pathway or the PTEN/Akt signal pathway in ESCC ( 59 ).…”
Section: Roles Of Exosome In the Initiation And Development Of Esccsupporting
confidence: 70%
“…Among the biomolecules carried by EVs, miRNAs have been found to play roles in tumor-induced inflammation, angiogenesis and immune modulation to facilitate tumor spreading, and tumor escape from immune surveillance [ 34 ]. Modulation of cellular miR-21 levels has been shown to cause changes in chemo-sensitivity [ 31 ], however direct evidence of EV-mediated modulation of chemo-sensitivity via miR-21 expression remains elusive, in contrast to the more widely available indirect evidence based on cancer cell proliferation rates [ 35 ]. Ren and colleagues verified that EVs from hypoxic mesenchymal stem cells promote NSCLC growth by delivering miR-21, which downregulates PTEN [ 36 ].…”
Section: Discussionmentioning
confidence: 99%